Respuesta :

Answer: 1


Step-by-step explanation: You are starting with (a, b)

(a, -5) means that when b is -5, a is a

So substitute-5 into the equation for b and solve for a  

3a = -2b - 7

3a = -2(-5) - 7

3a = 10 - 7

3a = 3

a = 1


Answer:

a = 1

Step-by-step explanation:

Given : If (a,-5) is a solution to the equations 3a=-2b-7,

To find : what is a

Solution : We have given

(a,-5) is a solution to the equations 3a=-2b-7,

For a = a and b = -5.

3a = - 2(-5) - 7.

3a = 10 -7 .

3a =  3.

On dividing both side by 3.

a = 1

Therefore, a = 1

RELAXING NOICE
Relax